Public Perception of English Environmental Taglines in Indonesian Retail Campaigns: Between Global Messaging and Local Meaning - Tanasy, Novalia; Zul Astri; Nurul Fachrunnisa (Institut Agama Islam Negeri Palopo, 2025)
Taglines are widely used in environmental media campaigns and appear in various formats such as posters, flyers, and tote bags. Despite their prevalence in Indonesia, public awareness of environmental protection remains limited. This study investigates the use of English in environmental campaign taglines, focusing on how these taglines are perceived by the public and their effectiveness in influencing environmentally conscious behavior. Employing a qualitative research approach, data were collected through semi-structured interviews with 15 participants across three public locations. Thematic analysis revealed that participants’ perceptions of English-language environmental taglines are shaped by emotional connection, cultural relevance, and language accessibility. English is often appreciated for its clarity, simplicity, and global resonance, but local languages are perceived to offer stronger emotional and cultural connections. Most participants found that English taglines increased awareness, and in some cases motivated behavioral changes, such as reducing plastic use. However, linguistic barriers and cultural disconnect were also noted, particularly among individuals less familiar with English. These findings suggest that while English taglines can effectively promote environmental awareness, their success depends on balancing global appeal with cultural and linguistic sensitivity to local audiences.